The Role Mediation in Improving Workplace Spirituality - Aprilia, Suci; Palupiningdyah, Palupiningdyah (Universitas Negeri Semarang, 2019)
This study aimed to examine the effect of Workplace spirituality and Perceived Organizational Support on Employee Performance Through Work Engagement Study on the production employees of PT. Busana UtamaTextile Buaran Pekalongan. The type and design of research used in this research is quantitative research. The population in this study was 237 employees. The samples in studies using probability sampling techniques, obtained the sample size should be used 149 employees. Collecting data using a questionnaire that measured with the Likert scale. Data analysis using partial test and path analysis using SPSS version 23. Data were collected through interviews, questionnaires, and literature study. Results from the study showed that workplace spirituality has a positive effect on employee performance. Results also showed perceived organizational support positive effect on employee performance. As for the influence of workplace spirituality and perceived organizational support on work engagement has a positive effect. In addition, the work engagement proved to mediate the relationship between workplace spirituality on employee performance and relationships perceived organizational support on employee performance.